PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ADOBE FLASH PROFESSIONAL CS6 PADA PEMBELAJARAN TEMATIK KELAS IV - Ramadhani, Arif; Kartono, Kartono; Sabri, Tahmid (Universitas Tanjungpura, 2023)
This study aims to produce a product in the form of a validated interactive multimedia based on Adobe Flash Professional CS6. The research method used is research and development (RD) by adapting the Borg and Gall design development model. The research development procedures are preliminary studies, data collection, product design, design and material validation, design and material revision, product trials, and product revisions. The types of data used in this research are qualitative data and quantitative data. Data collection techniques in this study were observation, interviews, and questionnaires. The research instrument chosen by the researcher in this study consisted of observation, interviews, and questionnaires. The data analysis technique in this study was carried out with qualitative data analysis techniques and quantitative data. The results showed that the research development process was a preliminary study, data collection, product design, design and material validation, design and material revision, product testing and product revision. With the feasibility level of interactive multimedia developed is very good in terms of design and material aspects with an average value of 3.70 and 3.68 and the results of product trials are very good with an average value of 3.55. Thus the interactive multimedia product developed is very suitable for use in learning.